Analiza porównawcza służby cywilnej w Polsce i w instytucjach Unii Europejskiej (stan prawny – grudzień 2008 rok) - Jurga-Wosik, Ewa (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
The civil services in Poland and EU institutions undergo similar processes. France (at the time of the 3rd Republic) was the cradle of civil service, therefore the administrative systems ofWestern Europe (and others) have sought examples there. The Polish model of civil service can be described as a mixed one, with the prevalence of regulations typical of a career model. In the career model the state is the master that employs a servant. Similar solutions are applied in France, Germany and Austria. They have been modified for the purpose of the specific functions which the civil service performs in EU institutions (a so-called closed career model). In the position system, particular authority is granted the civil servant’s employer rather than the state as a whole. A civil servant is employed in a particular position rather then in the civil service ‘in general’. The stability of employment and guarantee of remuneration are lower. The UK, Nordic countries and Italy apply solutions that are similar to this model.